Fig. 17 in Cambrian microfossils from glacial erratics of King George Island, Antarctica ... - Wrona, Ryszard (Zenodo, 2004)
Fig. 17. Diagrammatic reconstruction of the Hadimopanella antarctica Wrona sclerite in oblique lateral (A) and dorsal (B) views; see also Wrona (1987). C. Energy dispersive spectrum (EDS) for the H. antarctica sclerite. ... : Published as part of Wrona, Ryszard, 2004, Cambrian microfossils from glacial erratics of King George Island, Antarctica, pp. 13-56 in Acta Palaeontologica Polonica 49 (1) on page 40, DOI: 10.5281/zenodo.13285795 ...